2014
DOI: 10.1002/job.1945
|View full text |Cite
|
Sign up to set email alerts
|

Care and career: A family identity‐based typology of dual‐earner couples

Abstract: The rise of dual-earner couples challenges traditional gender stereotypes of women as "caregivers" and men as "breadwinners" and significantly impacts the ways in which partners define their roles as family members. The way in which individuals construe their family identities has implications not only for the decisions they make at home but also decisions in the workplace. In this paper, we propose an updated understanding of the different ways in which men and women can construe their family identity-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(144 citation statements)
references
References 87 publications
3
135
0
6
Order By: Relevance
“…However, these programmes had indirect effects, mediated by individuals' 'PA' and 'LCS', on helping improve employee's overall well-being. In particular, organisational WLB coping programmes appear to increase employees' problem-solving abilities and provide emotional support (Allvin, 2008;Masterson & Hoobler, 2014;Pienaar, 2008). The results from the current study found that the non-monetary-based organisational WLB coping programmes (i.e.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…However, these programmes had indirect effects, mediated by individuals' 'PA' and 'LCS', on helping improve employee's overall well-being. In particular, organisational WLB coping programmes appear to increase employees' problem-solving abilities and provide emotional support (Allvin, 2008;Masterson & Hoobler, 2014;Pienaar, 2008). The results from the current study found that the non-monetary-based organisational WLB coping programmes (i.e.…”
Section: Discussionmentioning
confidence: 59%
“…Stressful situations may also arise when dual-earner couples try to manage their spouse'/partner's work commitments (Lapierre & Allen, 2012;Masterson & Hoobler, 2014). For example, Premeaux, Adkins, and Mossholder (2007) found that the existence of a partner/spouse without work commitments helped reduce the drain of resources on an individual and provided support in conflict situations.…”
Section: Individual Coping Strategiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter is particularly salient in the context of women's increased labor force participation, as it is not uncommon for both adult partners in a household to have career ambitions. Western societies have witnessed a steady increase in dual-earner households and non-traditional gender roles in recent decades (e.g., Haddock, Zimmerman, Lyness, & Ziemba, 2006;Marks, 2006;Masterson & Hoobler, 2015), and as the traditional single-wage earner model fades, decision-making in the work domain increasingly is affected by family factors. We therefore believe that the shift toward dual-earner families has important implications for the study of work decisions.…”
Section: Introductionmentioning
confidence: 99%